Aggression and Older Adults: News Media Coverage across Care Settings and Relationships. Issue 3 (10th September 2021) - Funk, Laura M.; Herron, Rachel V.; Spencer, Dale; Thomas, Starr Lee
ABSTRACT: Systematic, in-depth exploration of news media coverage of aggression and older adults remains sparse, with little attention to how and why particular frames manifest in coverage across differing settings and relationships. Frame analysis was used to analyze 141 English-language Canadian news media articles published between 2008 and 2019. Existing coverage tended towards stigmatizing, fear-inducing, and biomedical framings of aggression, yet also reflected and reinforced ambiguity, most notably around key differences between settings and relations of care. Mainstream news coverage reflects tensions in public understandings of aggression and older adults (e.g., as a medical or criminal issue), reinforced in particular ways because of the nature of news reporting. More nuanced coverage would advance understanding of differences among settings, relationships, and types of actions, and of the need for multifaceted prevention and policy responses based on these differences.